THE EFFECT OF JUMBLED TEXTS TOWARDS STUDENTS’ ABILITY IN WRITING IN SMPN 3 TANJUNG - Yunita Astuti; Tri Setianingsih (Universitas Islam Lamongan, 2018)
The aim of this research was to find out whether jumbled texts have any effects towards students’ ability in writing. This study was experiments research and used pre-test and post-test non-equivalent group design of quasi experimental design. The population of this study was all students of the second grade at SMPN 3 Tanjung and the sample was two classes which consisted of 22 students of each class. To analyze the data this study used descriptive statistic and inferential statistic. The finding of this research showed that the t-test was 3,416 > t-table 1, 682. The mean score of experimental and control group was 760>60,59. It can be concluded that alternative hypothesis was accepted and null hypothesis was rejected and jumbled texts was effective toward students’ ability in writing.Keywords: Jumbled Texts, Ability, Writing